Data set on volatile compound of coffee flowers at different annual rainfall - Tati Suryati Syamsudin; Hafsah Hafsah; Iriawati Iriawati (Data in Brief, 2019)
This data informs about the profile of volatile compound of coffee flower (Coffee arabica) from different locations with different annual rainfall by using gas chromatography - mass spectrometry (GC-MS). The volatile compounds were captured by solid phase micro extraction (SPME) methods. The extract then subjected to GC-MS for separation and identification of compounds. The profile of volatile compound was provided in, Table 1, Table 2, Table 3 and Table 4. Keywords: Altitude, GC-MS, Metabolite profiling, Microclimate, SPME